Iron-Based Metal-Organic Frameworks as Multiple Cascade Synergistic Therapeutic Effect Nano-Drug Delivery Systems for Effective Tumor Elimination - Heming Zheng; Guanghui An; Xiaohui Yang; Lei Huang; Nannan Wang; Yanqiu Zhu (MDPI AG, 2024)
Efforts have been made to improve the therapeutic efficiency of tumor treatments, and metal-organic frameworks (MOFs) have shown excellent potential in tumor therapy. Monotherapy for the treatment of tumors has limited effects due to the limitation of response conditions and inevitable multidrug resistance, which seriously affect the clinical therapeutic effect. In this study, we chose to construct a multiple cascade synergistic tumor drug delivery system MIL−101(Fe)−DOX−TCPP−MnO2@PDA−Ag (MDTM@P−Ag) using MOFs as drug carriers. Under near-infrared (NIR) laser irradiation, 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) and Ag NPs loaded on MDTM@P−Ag can be activated to generate cytotoxic reactive oxygen species (ROS) and achieve photothermal conversion, thus effectively inducing the apoptosis of tumor cells and achieving a combined photodynamic/photothermal therapy. Once released at the tumor site, manganese dioxide (MnO2) can catalyze the decomposition of hydrogen peroxide (H2O2) in the acidic microenvironment of the tumor to generate oxygen (O2) and alleviate the hypoxic environment of the tumor. Fe3+/Mn2+ will mediate a Fenton/Fenton-like reaction to generate cytotoxic hydroxyl radicals (·OH), while depleting the high concentration of glutathione (GSH) in the tumor, thus enhancing the chemodynamic therapeutic effect. The successful preparation of the tumor drug delivery system and its good synergistic chemodynamic/photodynamic/photothermal therapeutic effect in tumor treatment can be demonstrated by the experimental results of material characterization, performance testing and in vitro experiments.